Professional ethics (14.04.02) electronic course - Sukhikh, E. S. specialist in the field of nuclear energy Associate Professor of Tomsk Polytechnic University, Candidate of Physical and Mathematical Sciences 1986- (TPU Moodle, 2025)
The aim of this course is to develop students' ability to adequately analyse and resolve complex ethical issues arising in the course of professional activity, as well as to develop skills in documentation and correspondence in accordance with ethical standards. Students will be taught to organise discussions of research results and professional activity, taking into account the diversity of cultural and social contexts. The course also aims to develop skills in maintaining medical and technical documentation with an emphasis on professional ethics, as well as to create tools for automating calculations and data analysis in compliance with ethical standards and requirements